Status gizi berdasarkan dialysis malnutrition score (DMS) dengan kualitas hidup pasien hemodialisis - Dina Maulina Hayati; Fery Lusviana Widiany; Fera Nofiartika (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2021)
Nutritional status based on the dialysis malnutrition score (DMS) with hemodialysis patients' quality of lifeBackground: Chronic kidney disease (CKD) is a disorder of the kidney organs characterized by abnormalities in the structure or function of the kidneys. Patients suffering from end-stage CKD require renal replacement therapy in the form of hemodialysis. However, hemodialysis on a routine basis can decrease nutritional status, which will result in malnutrition patients. Malnutrition is associated with morbidity and mortality rates, such as prolonged weakness, susceptibility to infectious diseases, and impaired wound healing that can affect the quality of life. Objective: This study aims to determine the correlation between nutritional status based on the Dialysis Malnutrition Score (DMS) with the quality of life of hemodialysis patients. Methods: The research design was cross-sectional with an observational research design. This research was conducted from 02 September 2019 until 11 September 2019 in the hemodialysis unit at RSUD Panembahan Senopati Bantul with 182 subjects of all chronic kidney disease patients undergoing hemodialysis from 2009 until April 2019. The researcher assessed nutritional status data based on the DMS. In addition, the quality of life was based on Kidney Disease Quality of Life (KDQoL) which researchers for elderly subjects assisted, and some parts filled directly by the subject. The statistical analysis used for this study was the Chi-square test. Results: Based on the Chi-square test, there is a correlation between nutritional status based on the DMS and the quality of life of hemodialysis patients (p-value=0.009). Most subjects had good nutritional status based on the DMS and had good quality on the KDQoL. Conclusions: There is a correlation between the risk of malnutrition based on the Dialysis Malnutrition Score (DMS) and hemodialysis patients' quality of life (KDQoL).